Negotiating privately for an effective role in public space : a case study of women in Panchayats of Orissa, India - Miśra, Hiraṇmaẏī (Cambridge Scholars Publishing, 2013)
This is the outcome of interdisciplinary research investigating female participation in politics in rural India